Relationship between soil salinity and alkalinity with Alhagi camelorum growth in hypersaline and hyperarid environments. (November 2022) - Pirasteh-Anosheh, Hadi; Parvizi, Hossein; Parnian, Amir; Esfahan, Ehsan Zandi; Ranjbar, Gholamhassan; Bhardwaj, Ajay Kumar
Abstract: In this research, the growth and distribution of Alhagi camelorum Medic. as a potential crop was monitored for producing forage in hypersaline and hyperarid regions. For this purpose, seven Alhagi- dominated rangelands were selected in its original homeland at the south of the Great Salt Desert. The soil salinity of selected regions is very variable, and ranged from 3.6 dS m −1 to 725 dS m −1 and from 0.4 dS m −1 to 366 dS m −1 at 0–30 cm and 30–60 cm soil depths, respectively. The annual mean of maximum and minimum air temperature is around 30 and 6 °C, respectively, and the mean annual precipitation is less than 150 mm. The plant growth characteristics assessed by canopy cover, canopy height, shoot fresh weight (SFW), and dry weight (SDW) had a negative relationship with soil salinity and pH. The highest SFW (24.97 t ha −1 ) and SDW (6.98 t ha −1 ) of Alhagi were obtained where soil salinity was 13 dS m −1 and soil pH was the lowest (7.1). Alhagi maintained the minimal growth and production of 20 cm canopy height and 50% canopy cover even in the saltiest conditions with a soil salinity of 395 dS m −1 ; hence it can serve as a potential crop for haloculture systems. In Aqda, the canopy cover increased with increase in the soil salinity up to 7–10 dS m −1 but decreased as the salinity levels increased further. The study revealed that A. camelorum not only has a very high tolerance to salinity but a moderate salinity up to 10 dS m −1 can also stimulate the growth. However, soil pH had a greater effect on growth, and Alhagi does not have a high tolerance to soil alkalinity. Therefore, Alhagi species could not be a bio-indicator for soil salinity, while well-established plants with good canopy could be considered as a sign for low alkalinity in arid terrestrial ecosystems. Highlights: Established Alhagi plants maintained could survive at hyper-dry and hypersaline ecosystems. Soil salinity in Alhagi rangelands was up to 129 (0–30 cm) or 65 g kg −1 (30–60 cm). Alhagi does not have a high tolerance to soil alkalinity. Alhagi could be a potential option for biosaline agriculture or haloculture. Well-established Alhagi plants with good canopy could be bio-indicator for low alkalinity ecosystems.